A STUDY ON GREEN HRM: A NEW DEVELOPMENT IN HR METHOD - Oberoi, Kirti; Saha, Jhuma (ShodhKosh: Journal of Visual and Performing Arts, 2024)
Green Human Resource Management has been regarded by means of revolutionary concept in organizational managerial cultures, wherein the concepts of environmental administration and elementary tasks of the human resource management are incorporated. This paper seeks to look at Green HRM in relation to its development, incorporation and its effects to organizations today. Most of these measures comprise of green recruitment, green training, green performance appraisal as well as measures being sought by the organization, entity or company are green measures aimed at reducing the ecological footprint of the organization. In the study, factors that drive, limit and the potential of Green HRM are listed with special reference to its positive impact on members of staff engagement, organizational effectiveness and sustainable utilisation of resources. This paper also presents a assessment of the state of the art on Green HRM, which provides firms with a reference guide on how to link their green human resource management with administrative environmental administration initiatives. Research therefore provides literature review on previous sustainable business studies to propose Green HRM as a significant tactic to sustainable environment and organizational presentation.